Teaching models in inTerneT learning, a look inTo The archiTecTure of virTual courses and Their Tendencies - Cortes Mendez, Jairo Alonso; Lozano, Jairo Oswaldo (Ingeniería Solidaria, 2012)
This paper presents partial results of a research project, approved by Conadi of the Universidad Cooperativa de Colombia, 2010 call for research projects, called “Social networks; a teaching strategy in learningenvironments from higher education”, subscribed to the Anta group, registered and rated by Colciencias (since it has shown partial results it is currently in the “others” category). The general objective of theresearch project is to develop a methodological proposal, based on the use of multimedia technology, and social networking and connectivity software, to improve learning environments in higher education. Theauthors analyze an ideal structure for virtual courses, detailing each of their parts, specially the theories of David Merrill and Robert Gagné, precursors of instructional design; through this study, they move forwardin their proposal to create a virtual learning environment for the engineering faculty of the Bogota branch.
Keywords: personal learning environments; architecture; virtual education; teaching models; Web